Association between single nucleotide polymorphisms of the DNA mismatch repair gene hMSH2 and postmenopausal breast cancer in Polish women - Samulak, Dariusz; Romanowicz-Makowska, Hanna; Smolarz, Beata; Połać, Ireneusz; Zadrożny, Marek; Westfal, Bogusław; Sporny, Stanisław (Menopause Review/Przegląd Menopauzalny, 2012)
Background : Mutations in the hMSH2 gene predispose to a number of tumorigenic conditions, including breast cancer. hMSH2 encodes a protein in the mismatch repair (MMR) pathway which is involved in the removal of mispairs originating during replication or from damaged DNA. Material and methods : The genotype analysis of Gly322Asp and Asn127Ser hMSH2 gene polymorphisms for 205 breast cancer patients and 180 controls of cancer-free subjects in the Polish population was performed using the PCR-based restriction fragment length polymorphism (PCR-RFLP). Results : The distribution of genotypes of the Gly322Asp polymorphism of hMSH2 in patients differed significantly (p < 0.05) from those predicted by the Hardy-Weinberg equilibrium. There were significant differences in the frequencies of alleles between breast cancer subjects and controls (p < 0.05). The Asp/Asp genotype of hMSH2 increased the risk of breast cancer occurrence (OR 2.60, 95% CI 1.03-6.53, p = 0.043). Conclusion : The results support the hypothesis that the Gly322Asp polymorphism of the hMSH2 gene may be associated with the incidence of sporadic breast cancer in Polish women.